Meningkatkan Personal Finance Management Siswa SMA PGRI 2 Padang - Gumanti, Dessyta; Noer, Salman M; Respita, Reni; Lo, Caterina; Detman, Detman; Diovani, Serli; Astuti, Widya; Irman, Irman (Journal of Community Service and Society Empowerment, 2025)
Personal finance management is very important, especially for the younger generation such as students, for their future. However, in reality, there are still many students who do not understand how to manage finances effectively. Community service activities are carried out for students of SMA PGRI 2 Padang with the hope that students will be able to manage their personal finances from an early age. This activity is carried out through a series of workshops and interactive discussions that involve students in activities based on good financial planning and management. Through a simple and practical approach, students are invited to learn the basic concepts of money management, create a personal budget, and understand the importance of saving and investing. The results of this service show an increase in students' understanding of the importance of personal financial management and their ability to plan a more structured budget.